Paucity of viral infection symptoms in patients with immune-mediated inflammatory diseases - Carola Berking; Georg Schett; Andreas Ramming; Raja Atreya; Markus F Neurath; Bernhard Manger; Filippo Fagni; Arnd Kleyer; Milena L Pachowsky; Axel J Hueber; Stefan Kleinert; Karin Manger; et al. (BMJ Open)
Objectives Although patients with immune-mediated inflammatory diseases (IMID) are thought to be more susceptible to viral infections, it is unclear whether their presentation differs between patients with IMID and healthy controls. This study aimed to investigate the symptom pattern of common viral infections in patients with IMID and compare it with controls without IMIDs.Design A cross-sectional study conducted between 1 February and 30 April 2020, using a questionnaire.Setting Seven tertiary regional care centers in Germany, which specialised in the care of patients with IMID (namely, in gastroenterology, dermatology, rheumatology and immunology clinical care).Participants One thousand nine hundred nine participants completed the survey (757 patients with IMID; 1152 non-IMID controls).Primary outcome measure The occurrence of 11 common viral illness symptoms within the preceding 3 months in patients with IMID and non-IMID controls.Results Symptom data were clustered, based on number and co-occurrance, into 3 major clusters and 2 subclusters ranked by the average number of symptoms. Patients with inflammatory bowel disease and psoriasis were significantly overrepresented in the lower-frequency subcluster of the polysymptomatic cluster. Patients with rheumatoid arthritis were overrepresented in the lower-frequency subclusters of the intermediate and oligo-/asymptomatic clusters. Controls were over-represented only in the higher-frequency subclusters of each major cluster where none of the IMIDs were over-represented. Spondyloarthritis and other IMIDs were also overrepresented in the low-frequency subcluster, but the results were not significant. Overall, patients with rheumatoid arthritis patients reported fewer symptoms (rate ratio=0.68, 95% CI, 0.59 to 0.80) than non-IMID controls.Conclusion Patients with IMID are over-represented in low-frequency subclusters, even among individuals who have reported a broad range of viral infection symptoms. This pattern suggests that the manifestations of viral infections are different between patients with IMID and controls, thus challenging the accurate and early diagnosis of infections.